Prevalence of Perinatal Asphyxia with Evaluation of Associated Risk Factors in a Rural Tertiary Level Hospital (KYAMC Journal, 2017)
Background: Perinatal asphyxia (PNA) is one of the most important causes of perinatal mortality and morbidity which can be preventable and managable.Objectives: The purpose of the study was to determine the prevalence of perinatal asphyxia and to explore the factors influencing or related to the development of the PNA.Materials and Methods: It is a cross-sectional study conducted in the neonatal unit of department of pediatrics, KYAMC hospital from January 2015 to December 2016. Two hundred eleven neonates admitted in neonatal unit including SCABU were enrolled in the study considering inclusion criteria. Necessary information about sociodemography, peri-natal history (including antepartum, intrapartum and fetal risk factors) were collected by detailed history taking on a pre-designed questionnaire. Clinical examinations and outcomes were also recorded. We used Student's t-test and ?2-test to determine the association of PNA with various risk factors.Results: The male to female ratio was 1.6:1. The mean age of the neonates during admission time was 3.66 (±5.506) days (in PNA 1.8±2.803 days and in normal group 6.11±7.047 days). The overall prevalence of PNA was 56.9% (120); male 60.8% (73) and female 39.2% (47). Identified significant materno-fetal risk factors were maternal young age (p= .038), low socioeconomic condition (p = .000,) primiparity (p = .003), muconium stained amniotic fluid (p = .004), obstructed labour (p = .019), low birth weight (p = .009) and home vaginal delivery by local dai and midwives (p = .017). Serious neonatal complications noted among the asphyxiated babies were hypoxic ischemic encephalopathy with convulsion, neonatal jaundice, septicemia, transient tachypnoea of neonate, hypoglycemia, respiratory distress syndrome, caput succedaneum and feeding problem.Conclusions: Findings of this study highlight the need for the better obstetrical care and awareness of the possible presence of the risk factors of PNA among mothers and fetus, so that the occurrence and worsening of PNA could be prevented or at least appropriately managed. It can reduce the high incidence of morbidity and mortality due to birth asphyxia.KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 43-48